Unlimited Riches: Making Your Fortune in Real Estate Investing - Shemin Robert (John Wiley, 2002)
As far as reliable investments go, real estate is the best wealth-builder in the universe. In Unlimited Riches, bestselling author and mega-successful real estate investor Robert Shemin shares his proven techniques for investing in this powerful asset. He presents a step-by-step system that lets you understand and master the same techniques he employed to make his millions. With his expert guidance and a wealth of sample forms and example material, you’ll be on your way to Unlimited Riches in no time . . .